(untitled) (Medical Forum Monthly, 2022)
Objective: The rationale of our study is to evaluate the outcome of puerperal sepsis in patients undergone for caesarean delivery and this study will help us to save the patients from developing the sepsis and lessen the rate of maternal mortality. Study Design: cross sectional study Place and Duration of Study: This study was conducted at the Department of Obstet and Gynae, Peoples Medical College Hospital (PMCH) Nawabshah from January 2019 to November 2021 for a period of 10 months. Materials and Methods: Patients were admitted from Emergency Department. They were evaluated by taking detailed history and clinical examination. The patients having pyrexia/sepsis and delivered within 30 days were diagnosed on clinical examination apart from laboratory investigations. Patients were treated accordingly. Results: The age of patients was between 17-45 years. 10 (16.5%) age was between 17-20 years. 15 (24.5%) patients age was 21-30 years and 36 (59%) were of 31-45 years. 57 (93.4%) patients presented with increased leucocyte count , decreased platelets 41(67.2%), fever in 60(98.3%), abdominal distention in 50(82%), anemia positive in 50(82%), wound infection in 30(49%) and positive vaginal swabs in 39(64%). Patients developed septicemia in 17(27.8%), peritonitis in 26(42.6%), DIC in 14(23%) and mortality in 9(14%). Conclusion: It is concluded that patients presenting with puerperal sepsis after Caesarean delivery were of middle aged female, mostly un-booked, and complication commonly seen was peritonitis. As compared to other studies, mortality was decreased in our study.